Moderate Islamists as reform actors: Conditions and programmatic change - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2007)
Over the last years, Islamist movements and parties have more and more been able to translate their popularity into impressive election successes or victories, for example in Egypt, Iraq, and Palestine. In many states in what has been termed the "Broader Middle East," moderate Islamists are today the most important actors alongside current or former regime elites. Without doubt they will in the mid- to long term be forces to be reckoned with and will have greater influence on political decision-making processes than civil society or radical or terrorist groups.Although they mostly espouse socially conservative positions, they often make progressive demands when it comes to reform of the political system. It is often said that Islamist calls for democratization are of a purely tactical nature, and that, if they came to power, they would set about establishing authoritarian theocratic regimes. Indeed, the "risk" of political opening is that power could pass to forces where we cannot today know whether they will play by democratic rules. At the same time, however, it is obvious that political opening is not possible as long as it excludes those forces that have the greatest support among the population and often represent the only effectively organized alternative to authoritarian regimes.The contributions in this volume look at the cases of Iran, Turkey, Iraq, Algeria, Bahrain, Egypt and Palestine analyzing the questions: What are the priorities of Islamist actors? What do their reform agendas look like? To what extent have the agendas of Islamists changed over the course of participation in parliament or through taking on (shared) responsibility of government? Does the integration of Islamists lead to a stabilization of authoritarian rule or does it promote political opening? (SWP Research Papers)
Keywords: 320